(untitled) (Academic Journal of Internal Affairs, 2025)
Aim: The aim of the study is to provide an overview of the violent extremist insurgency in Mozambique’s Cabo Delgado province with a special emphasis on developments in 2023 and 2024. Methods: The study is based on the review of secondary literature, open-source information, as well as Armed Conflict Location and Event Data Project’s (ACLED) relevant data. Findings: The study confirms the recommendations of previous research regarding the importance of a holistic approach to anti-insurgency operations. The study found that despite achieving successes on the battlefield, the government of Mozambique has failed to address the root causes of the insurgency and to pursue a well-rounded policy which in turn allowed the insurgents to rebuild and conduct more operations in the first months of 2024. The study outlines the importance of adapting one’s approach to the devising and the implementation of an anti-insurgency strategy in response to changing circumstances and new information Value: By 2021, both scholarly and mainstream media took notice of the violent extremists’ activities which by that point had displaced over 800,000 people. However, with Mozambique’s call for help to the international community and a string of victories on the battlefield, the insurgency essentially disappeared from mainstream discourse. This study fills this gap and provides an up-to-date summary of the insurgency’s activities as well as tentative confirmation of the validity of previous research.